Measuring and Developing Color Aptitude of Students at High Schools - Perge, Erika (International Journal of Engineering and Management Sciences, 2018)
The tutoring project called „ Chromatic sensation” will be executed via the project of the University of Debrecen titled EFOP-3.6.1-16-2016-00022 „Debrecen Venture Catapult". The aim of this tutoring project is to develop the students’ sense of colour and their ability to communicate through the use of colours. Our project is recommended to high-school students who might want to engage their further education in the fields of engineering. This paper presents the results of our research where ability to sense brightness differences and saturation differences of students completed their high school studies were tested, and discusses our skill development tools and their applications as an integrated part of our research.